Detection of Unculturable Fungi in Soil Regions of Aziz Awa in Sulaimani province - Wijdan Ahmed Ali; Bahrouz M.M AL-Jaaf; SajidS.Saleam AL-SaeedI (Tikrit Journal of Pure Science)
Unculturable and non-sporulting fungi represent a great challenge in studying biotrophic, endotrophic and mycorrhizal fungal groups. In this study collection of soil sample from region Aziz Awa in sulaimani province and using culture-dependent and culture in-dependent techniques for cultivation of unculturable fungi for the purpose of expanding studies on fungal biodiversity in soil. Sabouraud Dextrose Agar with supplement as pyridoxine by replicating master plate from higher dilution of soil three tinny colonies (less than 1mm in diameter) had grown on medium after incubation for 5-7 weeks at 280C but had not shown growth when replicated on traditional mycological media (PDA, Czapack Dox Agar and Sabouraud Dextrose Agar) were selected, purified, studied culturally and microscopically and identified by molecular methods. Four specific primer sets (NSIF/ITS4r, NSIF/ LRIF, EF4F/ITS4r and EF60F/ITS4r) were used to amplify partial sequences of fungal r RNA gene included ITS sequences. The partial sequences of three clones were aligned through the BLASTN phylogenetic analysis in NCBI were available at GenBank database and revealed higher scores and identities with Fusarium sp, Penicillium sp and Uncultured soil fungus clone. These results led us to consider the clones as viable but non culturable (VBNC) soil fungi like the common phenomenon in some bacterial species.